Web-based assessment of information systems services quality in Malaysian government agencies - M. Masilamani, M. Poobalan (2005)
Conducting assessments using conventional techniques is time consuming, labour intensive and costly. Assessment data captured through conventional means requires conversion to electronic form, relevant storage mechanism, and data crunching to obtain summaries and reports. Assessing Information Systems Service Quality (ISSQ) moreover requires repetitive and continuous effort in order to improve service quality. In order to provide a solution to the above issues, this research firstly provides an understanding of assessment by identifying assessment elements through literature review on assessments conducted in various fields. The identified elements are assessment area, purpose, subject of assessment, measurement, results, and assessors. This is followed by development of a Model for Web-Based ISSQ Assessment that incorporates gap measurement from Gap Model. The model consists of the following components: service stakeholders, ISSQ elements, process, instrument, analysis, results and the Internet as a media of communication. A Web-Based ISSQ Assessment System Architecture is derived from the Model for Web-Based ISSQ Assessment. The architecture is used to develop a web-based ISSQ assessment prototype. Two case studies were conducted to test the model through the use of the prototype. The findings of the research are categorized into four parts. Firstly, it is found that the Model for web-based ISSQ Assessment is useful to the service providers of the case study organization as it provides a guideline for web-based ISSQ assessment. Secondly, gap measurement provides a simplified but useful means of assessing ISSQ by the stakeholders. Third, the addition of data mart and Online Analytical Processing (OLAP) cube enhances the value of assessment data. Finally, the research also shows that web-based assessment of ISSQ is applicable and practical, but requires good infrastructure support.